2019
DOI: 10.1177/2325967119880487
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Revision Anterior Cruciate Ligament Reconstruction and Frequency With Which Patients Change Surgeons

Abstract: Background:Revision surgery is a known complication after anterior cruciate ligament (ACL) reconstruction (ACLR), but the proportion of patients who seek a different surgeon for their revision procedure is unknown.Purpose:To determine the rate and risk factors for revision ACLR in New Zealand and to find the proportion of patients undergoing revision ACLR who see a different surgeon compared with their primary procedure as well as the factors that may influence this decision.Study Design:Case series; Level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 29 publications
1
27
1
1
Order By: Relevance
“…According to a widely accepted theory, younger, more active patients tend to put more demand on the graft; thus, increasing the risk of re-injury and elongation [ 29 ]. Lower age has been confirmed as a risk factor in several studies [ 9 , 14 , 29 , 30 ]; however, it was not significant at the 0.05 level in our analysis. It should be noted that our patient population consisted mainly of young adult athletes; adolescents and amateur sportsmen were excluded.…”
Section: Discussioncontrasting
confidence: 69%
“…According to a widely accepted theory, younger, more active patients tend to put more demand on the graft; thus, increasing the risk of re-injury and elongation [ 29 ]. Lower age has been confirmed as a risk factor in several studies [ 9 , 14 , 29 , 30 ]; however, it was not significant at the 0.05 level in our analysis. It should be noted that our patient population consisted mainly of young adult athletes; adolescents and amateur sportsmen were excluded.…”
Section: Discussioncontrasting
confidence: 69%
“…With regard to previous studies of the patient characteristics of patients who suffer an ACL re-rupture, several physically and surgically related risk factors have been identified. 27,28 Factors such as time from reconstruction to RTS have conflicting results, with studies reporting an association between an J o u r n a l P r e -p r o o f early RTS, before and 12 months after reconstruction, and an increased risk of ACL re-injury 12,14 and studies reporting no association. 29 A recent meta-analysis of studies from the Scandinavian Knee Ligament Registries reported that younger age (under 20 years), hamstring tendon, timing of surgery, associated medial collateral ligament injury and lower 2-year Knee injury and Osteoarthritis Outcome Score (KOOS) after primary ACL reconstruction are risk factors for undergoing an ACL revision.…”
Section: Discussionmentioning
confidence: 99%
“…Age <18 years, male sex, and a shorter time from injury to surgery (within 6 months) were found to increase the risk of revision. Similarly, Sutherland et al 21 found that younger age, male sex, and a shorter time from injury to primary surgery were associated with the risk of revision surgery, with a 5-year ACL graft survival rate of 95.5%. In contrast, in a long-term study, Grassi et al 7 could not identify any significant predictors for ipsilateral revision ACLR.…”
Section: Discussionmentioning
confidence: 88%